Geomorphological asymmetry of river basins belonging to different orders (based on the Belgorod region) - F.N. Lisetskii; Zh.A. Buryak; O.A. Marinina (Учёные записки Казанского университета: Серия Естественные науки, 2018)
The geomorphological analysis of the erosion potential of 52 sublatitudinal and 39 submeridional river basins within the boundaries of the Belgorod region has been performed. The asymmetry of each of them has been determined. A typology of paradynamical areas has been elaborated with the help of the digital elevation model, based on the objectively detected differences of exposure, vertical dissection, and joint influence of the length and steepness of slopes (relief function). The paradynamical areas comprise the geomorphological stages on the macroslope of the river basin. It has been shown that the most significant factors of integration of the paradynamical areas into the geomorphologically homogenous units are the relief function and vertical dissection. The effect of exposure differences occurs at a lower level of integration. The spatial orientation and order of the basin determine the features of asymmetry of its macroslopes. The asymmetry of submeridional basins appears only for the watercourses of V–VII orders, thereby indicating the scale limits of this regularity.